2023
DOI: 10.1111/1365-2435.14286
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal and host effects mediate the adaptive expansion and contraction of the microbiome during ontogeny in a holometabolous, polyphagous insect

Abstract: 1. Polyphagous, holometabolous insects adapt to rapid diet shifts imposed by their ecology and their life cycle. One shift is linked to development, as larvae and adults usually dwell and feed in different environments, using different resources.The second is caused by changes in larval hosts, often occurring at each generation. Studies show that the insect's microbiome also changes in relation to development and larval host. However, parental and larval host contributions to its structure and trans-generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 110 publications
2
12
1
Order By: Relevance
“…We suggest that the significantly higher α diversity observed in larvae from these farms also reflects the stochastic changes promoted by AKEs in stressed larvae. These results might also be in line with those of Jose et al [ 28 ] who reported higher α diversity in medfly larvae feeding on different fruits and lower diversity in adult mothers (in which they observed a strong bias towards high abundance of few bacterial species). We speculate that the effects related to fruit host in Jose et al [ 28 ] might also have been affected by AKEs, as larvae feeding on heterogeneous crops are allegedly subjected to heterogeneous levels of environmental stress.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We suggest that the significantly higher α diversity observed in larvae from these farms also reflects the stochastic changes promoted by AKEs in stressed larvae. These results might also be in line with those of Jose et al [ 28 ] who reported higher α diversity in medfly larvae feeding on different fruits and lower diversity in adult mothers (in which they observed a strong bias towards high abundance of few bacterial species). We speculate that the effects related to fruit host in Jose et al [ 28 ] might also have been affected by AKEs, as larvae feeding on heterogeneous crops are allegedly subjected to heterogeneous levels of environmental stress.…”
Section: Discussionsupporting
confidence: 92%
“…However, in tephritid agricultural pests, a crop effect is not always detectable as the dominant driver of microbial diversity. In fact, other and less obvious processes [ 28 ] and the effects of high spatial heterogeneity [ 29 , 30 ] interact as drivers of microbial diversity and contribute to the variability of patterns observed. The recent work of Jose et al [ 28 ] elegantly demonstrates how crop-induced adaptation and lineage-dependent maternal effects are two interacting drivers of microbial diversity in a cosmopolitan polyphagous fruit fly.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations